Exploration of realization of “timeliness” function of ecological restoration through judicial system - TIAN Qiyun, LI Binglin (Ziyuan Kexue, 2025)
The 2022 guiding cases of advance execution of ecological restoration reflect the urgent need for timely restoration in environmental litigation and highlight the necessity of establishing corresponding judicial mechanisms. However, due to the conflict between the requirement for clarity and the urgency of restoration, such cases are extremely rare. Therefore, to ensure the timely restoration of the ecological environment, it is necessary to demonstrate the theoretical legitimacy of excluding the clarity requirement from the conditions for obligating parties to carry out restoration before judgment. This study used logical and normative analysis methods to argue for the legitimacy of excluding the clarity requirement based on the principle of necessity. Since clarity is an institutional prerequisite for advance execution, the function of timeliness in ecological restoration can only be achieved within the injunction system. An injunction, by nature, is a judicial order compelling obligated parties to act or refrain from acting. While prohibitory injunctions (requiring inaction) have already been established through “conservatory injunction measures”, “ecological restoration injunctions” (requiring action) should also be incorporated into the scope of environmental protection injunctions. However, considering the practical need to balance interests, proof of case facts should not be completely excluded. Flexible provisions should be made in legislation, with case-by-case analysis.